2019
DOI: 10.2147/hp.s217955
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reperfusion Microvascular Ischemia After Prolonged Coronary Occlusion: Implications And Treatment With Local Supersaturated Oxygen Delivery</p>

Abstract: Following a prolonged coronary arterial occlusion, heterogeneously scattered, focal regions of low erythrocyte flow are commonly found throughout the reperfused myocardium. Experimental studies have also demonstrated the presence of widespread, focally patchy regions of microvascular ischemia during reperfusion (RMI). However, the potential contribution of RMI to tissue viability and function has received little attention in the absence of practical clinical methods for its detection. In this review, the anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…[20][21][22][23][24] Supersaturated oxygen (SSO 2 ) therapy shows potential for improving oxygenation and minimize infarction size. [25][26][27][28][29] Inflammation targeting methods after AMI have promising results in animal trials, and a randomized controlled trial (RCT) the Colchicine cardiovascular outcomes trial (the COLCOT trial) has demonstrated the beneficial effects of colchicine. [30][31][32][33][34][35][36][37] Targeting angiogenesis, using stem cells, biomaterials, and gene therapy, holds promise for regenerating myocardial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Supersaturated oxygen (SSO 2 ) therapy shows potential for improving oxygenation and minimize infarction size. [25][26][27][28][29] Inflammation targeting methods after AMI have promising results in animal trials, and a randomized controlled trial (RCT) the Colchicine cardiovascular outcomes trial (the COLCOT trial) has demonstrated the beneficial effects of colchicine. [30][31][32][33][34][35][36][37] Targeting angiogenesis, using stem cells, biomaterials, and gene therapy, holds promise for regenerating myocardial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Intracoronary hyperoxemic perfusion was associated with less endothelial cell edema and preserved endothelial nuclei ( Figure 6 ). SSO 2 treatment also prevented myocardial apoptosis ( 41 , 46 ).
Figure 6 Electron Micrographs of Porcine Myocardium in Control and SSO 2 -Treated Pigs Electron micrographs of porcine myocardium at 3 hours of reperfusion after 1 hour of occlusion in a control pig (left) and SSO 2 -treated pig (right) .
…”
Section: Sso 2 Therapy: Preclinical Studiesmentioning
confidence: 87%
“…Spears ( 41 ) has reviewed the concept of patchy regions of residual microvascular ischemia that remain in the reperfused bed, even after establishing patency of the MI-related culprit epicardial coronary artery, and the mechanisms behind this phenomenon. Specifically, reperfusion is typically heterogeneous within the microvasculature, resulting in patchy areas of residual ischemia/hypoxia in the ischemic risk zone.…”
Section: Sso 2 Therapy: Preclinical Studiesmentioning
confidence: 99%
“…Another ray of hope comes from the demonstration that pulmonary hypertension induced by hypoxic ventilation in young calves can be reversed by infusion of supersaturated oxygen-carrying saline solution [41]. Additionally reperfusion microvascular injuries of the heart following 30-minute coronary occlusion were also reversed in similar experiments [42].…”
Section: Intrathoracic Shunt In Covid-19 Patientsmentioning
confidence: 98%